Salinity stress effects on direct and indirect defence metabolites in maize - Forieri, Ilaria; Hildebrandt, Ulrich; Rostás, Michael Georg (Environmental and experimental botany, 2016)
In nature, plants are often exposed to multiple stress factors at the same time. The effects of single biotic or abiotic stresses on plant metabolism are well documented but how plants respond to a combination of these is little researched. Here we studied the effects of high salinity and herbivory on levels of secondary compounds and gene expression associated with defences against insects. Hydroponically grown maize plants were subjected to sodium chloride (1, 50, 100mM NaCl) and/or damage by caterpillars of Spodoptera exigua. Salt-stressed plants showed stunted growth, reduced chlorophyll fluorescence and enhanced levels of reactive oxygen species and 1,4-benzoxazin-3-one aglycones (aBX). Herbivory induced higher transcript levels of the Zm-Bx1 gene involved in aBX biosynthesis and of the Zm-SerPIN gene coding for a serine proteinase inhibitor which might affect plant feeding insects. Herbivory also triggered the emission of volatile organic compounds (VOCs) that are attractive signals for parasitoids and predators and thus regarded as an indirect defence. Herbivore-induced metabolites were differentially affected in salt-stressed plants. High salinity resulted in transient priming of jasmonic acid while aBX levels were reduced in double-stressed plants. Salt stress led to lower herbivore-induced VOC emission per plant but not per unit biomass. However, quantitative shifts in individual compounds were found in both cases. Our study confirms the notion that combined stresses produce a unique phenotype that cannot be derived from single-stress effects. The ecological implications of these changes for organisms from different trophic levels and for plant fitness remain to be tested.